Microplastics in the environment : from formation to remediation - Zhang, Xinxing (Wiley-VCH, 2025)
Authoritative reference addressing the characteristics, technologies, and solutions surrounding the most concerning environmental pollutant Microplastics in the Environment delivers a systematic and in-depth overview of microplastics generation mechanisms, risk prevention, and control solutions. Written by a highly qualified academic with significant research experience in microplastic pollution treatment, green polymer material functionalization, and recycling of solid waste, Microplastics in the Environment explores sample topics including: Characteristics of microplastics, such as their large specific surface area and small size, resulting in the formation of composite contamination New microplastics blocking approaches and technologies, and the mechanism of microplastics generation under the coupling effect of multiple environmental factors Transport and migration of microplastics, as well as their ecotoxicity to organisms in various environments, especially the complex estuarine environment The current state of plastic production, with insight on how society can find solutions to the expanding plastics industry Microplastics in the Environment is an essential reference on the subject for polymer chemists, materials scientists, environmental chemists, plastics technologists, and ecotoxicologists, as well as all professionals in the plastics industry, especially those focused on sustainability.
Keywords: Microplastics.; elektronické knihy; electronic books